High Mate Value Men Become More Accepting of Intimate Partner Abuse When Primed With Gender Equality - Blake, Khandis R.; Brooks, Robert C. (Frontiers in Sociology, 2018)
Although attempts to rectify intimate partner violence (IPV) predominantly target gender inequality as its socio-structural source, evolutionary insights cast doubt on the notion that gender equality unambiguously lessens IPV. Here we test whether the effect of gender equality on male-to-female IPV will depend upon men's relative position in the sexual marketplace (i.e., their mate value). We primed 350 subjects (218 men) with one of three different prime types (high or low gender equality, or neutral control) each replicated five ways (total 15 primes). We measured support for coercive IPV and attitudes to abortion (to see if gender equality cues men's urges to control female reproduction). Mate value moderated the effect of gender equality on men's (but not women's) attitudes toward IPV, and there was no effect for abortion. High-value men were supportive of IPV in conditions of gender equality, yet we found the reverse for low-value men. We interpret our results in light of the fitness costs and benefits IPV poses to perpetrators in high and low gender equality environments. Our findings show that phenotypic plasticity in male-to-female IPV can depend upon both broader socio-structural conditions between men and women and on an individual man's position in the sexual marketplace.